PERLINDUNGAN ANAK DALAM KONFLIK PERANG: ANALISA HUKUM HUMANITER - M. Syafi'ie . (Universitas Wahid Hasyim Semarang, 2013)
Abstrak Age children are sacred. They are the future assets. But the conflict has always made ​​them as victims. One of the children who drowned in the darkness of future war is a conflict. We witnessed how cruel conflict in Palestine-Israel war, the war in Iraq, the war in Yemen, War in the Congo, Conflict in Aceh, and several other areas. Thousands of children have been victims. Some are dead, wounded, lost relatives, and or disability. Their future is bleak. Therefore, the regulations, the children are always privileged protection. Included in the Geneva Convention, which is an international war rules. Children must be protected, and not involved in the conflict of war. If there is a violation, then the appropriate parties involved need to be prosecuted and tried according mikanisme fair trial. One of the trial is the International Criminal Court (ICC). Kata Kunci: Hukum Humaniter Internasional, Konflik Perang, Anak